Differences in Prostate Cancer Incidence and Mortality in Lower Saxony (Germany) and Groningen Province (Netherlands): Potential Impact of Prostate-Specific Antigen Testing - Kappen, Sanny; de Bock, Geertruida H.; Sirri, Eunice; Vohmann, Claudia; Kieschke, Joachim; Winter, Alexander (Frontiers in Oncology, 2021)
Background Prostate cancer (PCa) is the most frequent cancer among men in Europe. Differences in PCa incidence around the world can be partly explained by variations in recommendations for prostate-specific antigen (PSA), particularly for early detection. For example, the PSA testing policy is more conservative in the Netherlands than in Germany. To better understand the relationship between PSA testing recommendations and PCa incidence, stage distribution, and mortality, we compared these variables over time between Lower Saxony in northwestern Germany and the neighboring province of Groningen in the Netherlands. Methods Population data, tumor stage- and age group-specific PCa incidence (ICD-10 C61) and mortality rates for Lower Saxony and Groningen were obtained from the Lower Saxony Epidemiological Cancer Registry, the Netherlands Comprehensive Cancer Organization, and Statistics Netherlands for 2003–2012. Incidence and mortality rates per 100,000 person-years were age-standardized (ASR, old European standard). Trends in age-standardized incidence rates (ASIR) and mortality rates (ASMR) for specific age groups were assessed using joinpoint regression. Results The mean annual PCa ASIR between 2003 and 2012 was on average 19.9% higher in Lower Saxony than in Groningen (120.5 vs. 100.5 per 100,000), while the mean annual ASMR was on average 24.3% lower in Lower Saxony than in Groningen (21.5 vs. 28.4 per 100,000). Between 2003 and 2012, the average annual percentage change (AAPC) in PCa incidence rates did not change significantly in either Lower Saxony (−1.8%, 95% CI −3.5, 0.0) or Groningen (0.2%, 95% CI −5.0, 5.7). In contrast, the AAPC in mortality rate decreased significantly during the same time period in Lower Saxony (−2.5%, 95% CI −3.0, −2.0) but not in Groningen (0.1%, 95% CI −2.4, 2.6). Conclusions Higher PCa incidence and lower PCa-related mortality was detected in Lower Saxony than in Groningen. Although recommendations on PSA testing may play a role, the assessed data could not offer obvious explanations to the observed differences. Therefore, further investigations including data on the actual use of PSA testing, other influences (e.g., dietary and ethnic factors), and better data quality are needed to explain differences between the regions.